2008
DOI: 10.1142/s0218957708001912
|View full text |Cite
|
Sign up to set email alerts
|

Mild to Moderate Medial Collateral Ligament (Mcl) Injuries of the Knee: Sonographic Findings and Sonographic Valgus Stress Test

Abstract: The purposes of this study are to describe the sonographic findings of the injured medial collateral ligament (MCL) of the knee, to perform a sonographic valgus stress test, and to correlate these findings in order to advance the proper treatment for these patients. We examined 23 patients with clinical diagnosis of MCL injury. We evaluated proximal and distal MCL thickness, free fluid, and avulsion fractures. In addition, we performed a sonographic valgus stress test in the stress and rest positions. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Some differences between the results from the current study and those in the literature may be due to differences in loading. LaPrade et al [24] reported that gap width was measured during the application of a 10 Nm load, as in our study, whereas Kleinbaum and Blankstein [33] and Whelan et al [25] either did not control load or did not report it …”
Section: Figmentioning
confidence: 49%
See 2 more Smart Citations
“…Some differences between the results from the current study and those in the literature may be due to differences in loading. LaPrade et al [24] reported that gap width was measured during the application of a 10 Nm load, as in our study, whereas Kleinbaum and Blankstein [33] and Whelan et al [25] either did not control load or did not report it …”
Section: Figmentioning
confidence: 49%
“…This has clinical implications. For example, there is evidence that MCL-deficient knees show significantly greater values of absolute gap width compared with intact knees [24, 25, 33], and medial gap width may be a suitable method for assessing the efficacy of MCL repair [25]. Varus/valgus instability post-arthroplasty, which has been linked to patient satisfaction [11], and is often assessed clinically with radiographic examination, may also be possible to evaluate with ultrasound, though reverberation artifacts off of the metallic prosthesis [41] may make gap width measures more challenging in these cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the layers of the MCL are sonographically hyperechoic structures and are separated by a hypoechoic band, consisting of areolar tissue. This gives the MCL a trilaminar structure with the hyperechoic outer parts and a hypo-echoic inner part [ 7 8 9 18 19 ]. However, when injured, the trilaminar appearance is often lost and the MCL becomes hypoechoic and heterogenous, thought to be due to edema.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common mechanisms for knee injury is direct trauma, which is commonly seen in athletic injuries [ 3 ]. When injury occurs, the superficial MCL is the most commonly damaged ligament of the knee, usually induced by valgus stress, and can occasionally be accompanied by a tear in the medial meniscus [ 4 9 ]. While clinical examination is essential in diagnosing tears of the medial compartment of the knee, imaging is often required to make a conclusive diagnosis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%